1997
DOI: 10.1046/j.1365-2265.1997.1630976.x
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Positive Autoantibodies against Thyroid Peroxidase and Thyroglobulin in Patients with Sarcoidosis

Abstract: The data show a remarkably high incidence of thyroid autoantibodies in patients of middle of advanced age with sarcoidosis, especially in males, and a higher prevalence of Hashimoto's thyroiditis than in previous reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…11 However, larger studies have reported increased levels of TPOAbs in sarcoidosis patients. 8,10 In agreement with the latter, we also found significantly increased TPOAbs in female sarcoidosis patients compared to controls, and TPOAbs were significantly associated with clinical AITD.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…11 However, larger studies have reported increased levels of TPOAbs in sarcoidosis patients. 8,10 In agreement with the latter, we also found significantly increased TPOAbs in female sarcoidosis patients compared to controls, and TPOAbs were significantly associated with clinical AITD.…”
Section: Discussionsupporting
confidence: 77%
“…8 However, the results remain conflicting, with most of the published data limited to case reports, 9 and in only one study has a complete thyroid work-up been performed. 8 Controversy also exists regarding the presence of thyroid antibodies in sarcoidosis patients, with studies pointing to increased prevalence of antithyroid peroxidase antibodies (TPOAbs) and antithyroglobulin antibodies (TGAbs) 10 in sarcoidosis patients, while others have failed to document any differences. 11 Data concerning TSH receptor antibodies (TRAbs) are rather scarce, most of them derived from case reports; meanwhile, in a prospective study by Antonelli et al 12 the authors failed to demonstrate increased TRAbs titles in sarcoidosis.…”
Section: Introductionmentioning
confidence: 99%
“…A controlled study of 62 patients with pulmonary sarcoidosis reported that 27% had antibodies to thyroid peroxidase and/or thyroglobulin while 7.7%-9.1% of three separate control groups had antibodies (121). The patients with antithyroid antibodies were all older than 40 years of age and when this age group alone was analyzed, 55% of the men and 38% of the women were positive.…”
Section: Sarcoidosismentioning
confidence: 95%
“…Additionally 2 patients had insulin-dependent diabetes mellitus and 1 had premature ovarian failure (28,29). According to a Japanese study, a higher incidence of thyroid autoantibodies may be found in sarcoidosis patients with middle or advanced age and a high prevalence of Hashimoto's thyroiditis (30).…”
Section: Resultsmentioning
confidence: 99%